The depressurization of an expanded solution into aqueous media for the bulk production of liposomes - Meure, Louise A (Langmuir : the ACS journal of surfaces and colloids, 2009)
A new dense gas process for the formation of liposomes has been developed: depressurization of an expanded solution into aqueous media (DESAM). The technique provides a fast and simple process for bulk liposome formation. As an alternative to current dense gas technologies, the DESAM process reduces the pressure requirements for liposome formation. Liposomes with diameters between 50 and 200 nm were formed. For all samples produced using ethanol as the solvent, the average effective diameter ranged from 119 to 207 nm. When chloroform was used as the solvent, the average effective diameter increased to 387 nm. The residual solvent volume fraction in the liposomal product was less than 4% v/v, which is approximately one-quarter of the value reported for some other dense gas liposome formation methods. The liposomal samples were stored after formation at 5 degrees C for up to 8 months, with the average effective diameter and polydispersity increasing by only 13% and 7%, respectively, indicating high stability of the formulations